Rancang Bangun Solar Tracker Otomatis pada Pengisian Energi Panel Surya Berbasis Internet of Things (IoT) - Firmando Saragih; Realita Buaton; Magdalena Simanjuntak (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This study aims to design and develop an automatic solar tracker system based on the Internet of Things (IoT) to enhance the efficiency of energy collection in solar panels. The system utilizes key components such as the ESP32 microcontroller, LDR sensors, servo motors, and the Blynk platform to monitor performance in real-time. The solar tracker is designed to follow the movement of the sun, ensuring that the solar panels are always positioned optimally to receive sunlight throughout the day. Testing indicates that this system improves solar energy absorption efficiency compared to static solar panel systems. Furthermore, the integration of IoT allows for more effective and efficient remote control and monitoring. Thus, this technology not only offers improvements in energy efficiency but also provides a practical solution for better and more sustainable solar energy management.